Carburizing Surface Properties of Chromium-Molybdenum Alloy Steel for Automotive Crankshaft Sprocket and Pump Drive Hub - Yoo, Choon; Yoon, Sang-Jin; Oh, Chang-Yeol; Kang, Bo-An (International Journal of Engineering and Technology, 2018)
The purpose of this research was to investigate the affecting carburization of on the gas carburizing heat treatment layer of each material in the crankshaft sprocket and pump drive hub parts made of chromium-molybdenum alloy steel that are currently used in automobile engines. The effect of carbon potential, carburization time and diffusion time on surface hardness was mainly investigated.The specimen was the same size as the actual model used for the automobile parts and the carrier gas was made by injecting RX gas mixed with propane and air.The propane and butane gas were mixed and injected to control the carburizing gas environment, the steps divided into heat treatment for carburization and diffusion.The hardness of the carburizing depth of the heat treated automobile parts was measured with a micro Vickers hardness (HV 550) tester. As a result of the analysis of the specimen which was carburized from carbon content 0.20% Oil pump drive hub and 0.15% Crankshaft sprocket prototype, the carbon potential was high, the carburization time was longer and the surface hardness was high.From these results show that the lower the carbon content, the shorter the carburization time and diffusion time required to reach the required surface hardness and internal hardness. These are considered to be related to the carbon diffusion gradient on the surface and insideof the material.Also it was found that the carburization time and the carbon potential greatly affected the carburization hardness more than the carbon content. After the heat treatment, the surface texture was martensite and the internal structure showed a mixed structure of pearlite and ferrite. These results will be applied factory scale.Â Â Â